2022
DOI: 10.1126/sciadv.abm5667
|View full text |Cite
|
Sign up to set email alerts
|

Associations of plasma soluble CD22 levels with brain amyloid burden and cognitive decline in Alzheimer’s disease

Abstract: CD22 has been suggested to contribute to Alzheimer’s disease (AD) pathogenesis by inhibiting microglial amyloid β (Aβ) phagocytosis. Soluble CD22 (sCD22) generated by cleavage from cell membranes may be a marker of inflammation and microglial dysfunction; but alterations of sCD22 levels in AD and their correlation with AD biomarkers remain unclear. Plasma sCD22 levels were measured in cognitively normal non-AD participants and patients with preclinical AD and AD dementia from a Chinese cohort and the Australia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Inhibition of CD22 promotes microglial phagocytosis of Ab oligomers and lessens cognitive impairment in aged mice. The plasma levels of soluble CD22 are elevated in patients with Alzheimer’s disease, and its level was correlated with brain Ab burden, cerebrospinal fluid (CSF) p-tau levels, and baseline cognitive impairment ( 50 ). Therefore, increased levels of soluble CD22 are promising biomarkers of various disorders, including cancer, infections, and neurogenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CD22 promotes microglial phagocytosis of Ab oligomers and lessens cognitive impairment in aged mice. The plasma levels of soluble CD22 are elevated in patients with Alzheimer’s disease, and its level was correlated with brain Ab burden, cerebrospinal fluid (CSF) p-tau levels, and baseline cognitive impairment ( 50 ). Therefore, increased levels of soluble CD22 are promising biomarkers of various disorders, including cancer, infections, and neurogenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proven that the FGF8 [520], SERPINA1 [521], LRRK2 [522], CHRNA4 [523], TF (transferrin) [524], TRDN (triadin) [525], NR0B1 [526], RELN (reelin) [527], HTR2C [528], RIT2 [529], REN (renin) [530], TLR2 [531], MOBP (myelin associated oligodendrocyte basic protein) [532], TNR (tenascin R) [533], ADGRB1 [534], GPR37 [535], SHH (sonic hedgehog signaling molecule) [536], XDH (xanthine dehydrogenase) [537], SIRT2 [538], BMP2 [539], HAS2 [540], CSMD1 [541], NTF3 [542], SNCB (synuclein beta) [543], MMP3 [544], HLA-DRB5 [545], HLA-DRB1 [546], HLA-DRA [547], VWF (von Willebrand factor) [548], AKR1C3 [549], CASP1 [550], CHRNA5 [551], TET1 [552], LRRN3 [553], EGFR (epidermal growth factor receptor) [554], PLXNA4 [555], FOXG1 [556], MAP1B [557], ANK1 [558], ATP10B [559], RND3 [560], COMT (catechol-O-methyltransferase) [561], LIFR (LIF receptor subunit alpha) [562] and TRAF5 [212] are involved in Parkinson’s disease. Recent studies have shown that SERPINA1 [563], LRRK2 [522], CHRNA4 [564], CD22 [565], TF (transferrin) ssociated tyrosine kinase) [579], FGF14 [580], INSC (INSC spindle orientation adaptor protein) [581], BARHL1 [582], PRKCH (protein kinase C eta) [583], SLC24A4 [584], TMEM176B [585], MBP (myelin basic protein) [586], ACAN (aggrecan) [587], SHH (sonic hedgehog signaling molecule) [588], SIRT2 [589], RBP4 [590], ISM1 [591], HOXB6 [592], CDH13 [593], NTF3 [594], TRPC6 [595], MMP3 [596], HLA-DRB5 [597], HLA-DRB1 [546], CD74 [598],...…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study, higher plasma soluble CD22 (sCD22) levels are associated with accelerated cognitive deterioration. Furthermore, plasma sCD22 levels predicted longitudinal cognitive deterioration during 7.5 years of follow-up [ 51 ]. This evidence suggests that CD22 may be an important marker to help us identify patients who are more likely to transform from MCI to AD.…”
Section: Discussionmentioning
confidence: 99%